Research on the Path of Ethnic Minority Social Governance Construction under the Background of Rural Revitalization - Chen, Silian (Journal of Theory and Practice of Management Science, 2024)
Based on the strategic goal of rural revitalization, the policy goal of building a social governance community has become the guide of current scientific action. Ethnic minority villages need to combine their own regional characteristics, focus on social governance community, implement policy spirit, solve grassroots governance problems, and realize the choice of modern national governance system and governance capacity. We should improve the effectiveness of social governance, complete the integration of economic, cultural, ecological and environmental aspects, create beautiful and harmonious ethnic villages. During the epidemic, social entities such as enterprises, social organizations, and public welfare organizations other than the government also actively participated in the battle against the epidemic. When some traditional public service systems such as medical care, transportation, and distribution of living materials are forced to shut down or supply reduction due to the needs of epidemic prevention and control, various mobile Internet platforms give full play to their technological and business model advantages, autonomously allocate social resources, and coordinated with government departments, using online service platforms to ensure that residents start a new lifestyle of "no gathering and less contact". For example, Five major Internet medical service platforms includs Tencent United Medical Union, Penguin Almond, WeDoctor, Good Doctor Online and Dingxiang Doctor provide online free consultation, disease monitoring, intelligent hardware indicator collection and testing, out‐of‐hospital electronic prescription and medication guidance, drug delivery, etc. Provided medical services "without leaving home" for the general public and patients with mild illnesses for home isolation observation.